UPAYA PEMERINTAH MENGURANGI SAMPAH PLASTIK DI TULUNGAGUNG - Rohma, Na’is Natmisatur; Sari, Nurdiana Octavia; Ditia, Okta Wibi; Shakthi, Khodrat Srinalendra (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2023)
This study was conducted because of the generation of garbage that accumulates every day. Garbage is part of human life. Waste has a negative impact on the environment if left alone. Lack of public awareness of the existence of waste encourages an increase in the number of waste generation. Based on the publication of the Ministry of LHK, the total waste generation is 18.3 million tons per year. In Tulungagung in one day the assumption of waste produced reaches 600 tons, but DLH Tulungagung in per day can only handle 20% of the waste generated. Plastic bags are the largest contributor to waste waste management is an effort to reduce waste generation. An example is the existence of recycling processes and waste banks. In addition, plastic waste can be processed by applying the 3R concept (Reuse, Reduce, Recycle). With the above efforts, it is expected that waste, especially plastic waste, can be controlled